Human resource development research in tourism and hotel: a review of current literature and suggestions for future - Hosen, Sharif; Hamzah, Siti Raba’ah; Ismail, Ismi Arif; Alias, Siti Noormi; Abd Aziz, Mohd Faiq (Human Resource Management Academic Research Society, 2022)
The purpose of this paper is to provide a review of human resource development literature from the points of view of both human resource development and hospitality and tourism. The paper provides a critical, qualitative, and comparative review of HRD research literature on human resource development and hospitality and tourism, providing insights into emerging research trends and pointing to the gaps in the literature. The review result showed six streams of research from the hospitality and tourism literature: training design and work performance, individual factors and work performance, job satisfaction as a mediator, and qualitative reviews of the hospitality and tourism HRD literature. This review also points to the gaps between the two bodies of literature and gives recommendations for future research.